2011
DOI: 10.1159/000328739
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Combined Treatment with Irinotecan and S-1 (IRIS) in Patients with Inoperable or Recurrent Advanced Colorectal Cancer (HGCSG0302)

Abstract: Objectives: This phase II study was designed to evaluate the efficacy and safety of oral fluoropyrimidine S-1 plus irinotecan (IRIS regimen) in patients with previously untreated metastatic colorectal cancer. Methods: The response rate was the primary endpoint. Safety, progression-free survival time, and median survival time were secondary endpoints. The subjects were untreated patients with inoperable advanced colorectal cancer. Irinotecan was administered at a dose of 100 mg/m2 (on days 1 and 15).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…Regarding combinations with other oral 5-FU-derivative agents, several studies on the combination of S-1 and CPT-11 have been reported, mainly in Japan. Despite these being small-scale phase II studies, the outcomes of the IRIS regimen, typically combining S-1 with CPT-11, as the first-line therapy for advanced and/or metastatic colorectal cancer are favorable with an RR of 40-65%, a PFS of 7.8-8.6 months and an OS of 18.4 months, results similar to those obtained with the combination of capecitabine and oxaliplatin or CPT-11 [9,10,11]. In our previous clinical study using S-1 and CPT-11 as the first-line therapy at the same doses as in the present study, RR was 43.8% and OS was 17.9 months, and these results are similar to those reported in other studies [8].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Regarding combinations with other oral 5-FU-derivative agents, several studies on the combination of S-1 and CPT-11 have been reported, mainly in Japan. Despite these being small-scale phase II studies, the outcomes of the IRIS regimen, typically combining S-1 with CPT-11, as the first-line therapy for advanced and/or metastatic colorectal cancer are favorable with an RR of 40-65%, a PFS of 7.8-8.6 months and an OS of 18.4 months, results similar to those obtained with the combination of capecitabine and oxaliplatin or CPT-11 [9,10,11]. In our previous clinical study using S-1 and CPT-11 as the first-line therapy at the same doses as in the present study, RR was 43.8% and OS was 17.9 months, and these results are similar to those reported in other studies [8].…”
Section: Discussionmentioning
confidence: 85%
“…Because several other chemotherapy regimens combining CPT-11 and S-1 have been reported mainly in Japan [9,10,11], this combined chemotherapy appears to be one of the promising options in advanced and/or metastatic colorectal cancer. However, there have been few studies on the concomitant use of molecularly targeted drugs with the combination of CPT-11 and oral 5-FU-derivative agents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these phase II studies confirmed that irinotecan and S-1 combination therapy was effective as a first-line treatment [12], with clinical effects comparable or superior to those of FOLFIRI therapy. Jeung et al [18 ]found that a S-1 second-line monotherapy resulted in a 14.3% overall response rate and a 42.9% disease-control rate among patients for whom combined treatment with irinotecan or oxaliplatin had failed.…”
Section: Discussionmentioning
confidence: 77%
“…DPD inhibition in tumor cells has been suggested to contribute to an antitumor effect because S-1 has been reported to be effective against many solid tumors with a high expression of DPD [10]. Clinical response rates of 52.5-62.5% have been reported in phase II studies of irinotecan plus S-1 combination therapy (IRIS), with a median progression-free survival (PFS) of 7.8-8.6 months for its use as a first-line treatment for metastatic CRC [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Many drugs including 5-fluorouracil are known for their chemotherapeutic properties. Most chemotherapeutic agents show cellular toxicities which affect cancer as well as normal cells (17). Therefore, the development of new drugs showing low toxicities is required.…”
Section: Introductionmentioning
confidence: 99%